RANCANG BANGUN GENERATOR MAGNET PERMANEN FLUKS AKSIAL PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA BAYU (PLTB) SUMBU VERTIKAL - Adi Suryantara, I.M.; Indra Partha, C.G.; Sukerayasa, I.W. (Program Studi Teknik Elektro UNUD, 2024)
Axial flux permanent magnet generators are easy to manufacture because only the rotor and stator are aligned. Axial flux generators are one of the right choices for wind power plants due to the large number of magnetic poles, high electrical power density, and easy-to-increase power capacity. The axial flux type permanent magnet generator is designed with a speed of 600 rpm, a frequency of 50 Hz, a voltage of 12 V, a power of 7 Watts, 1 phase, 10 pairs of Neodymium Iron Boron (NdFeB) type magnetic poles, and 5 copper wire coils measuring 0.6 mm in diameter with a total of 301 turns. This vertical-axis wind farm test uses an axial flux permanent magnet generator with a 5? resistor load and is assisted by a blower. The blower is used to get a constant turbine rotation in accordance with the results of wind speed measurements taken for 3 days on the rooftop of the electrical engineering lecture building, namely the wind speed range of 3-5 m/s. Based on these tests, the generator is able to produce a voltage of 1.5 V, a current of 0.2 A, a power of 0.27 Watt, and a generator efficiency level of 0.63% at a wind speed of 3 m/s. It also produces a voltage of 4.4 V, a current of 0.7 A, a power of 2.77 Watt, and a generator efficiency level of 0.97% at a wind speed of 5 m/s.